The Protection of Tourism Sites as Cultural Heritage in Wetlands within the Framework of International Law - ALSAMARA, Tareck; GHAZI, Farouk; MALLAOUI, Halima (Journal of Environmental Management and Tourism, 2022)
The article deals with the protection of cultural heritage in wetlands under international agreements. It highlights the concept of the cultural and natural heritage of wetlands, and then discusses the protection of the world cultural heritage of wetlands within the framework of UNESCO.  The article also identifies cultural values under the Ramsar Convention. It focuses on the assessment of international protection of world cultural and natural heritage in wetlands. Finally, the article refers to the World Heritage of the Wilderness Wetlands. The article contributes to clarifying the absence of an independent legal framework for the protection of cultural heritage in wetlands. The Study concluded that international agreements do not establish explicit international obligations on states. Hence the need for an international convention dedicated to the protection of cultural heritage in wetlands. The study also concluded that there is no judicial mechanism to limit the deterioration of cultural heritage in wetlands.